A Systematic Review of Epidemiology and Risk Factors Associated With Chinese Inflammatory Bowel Disease - Cui, Guanglin; Yuan, Aping (Frontiers in Medicine, 2018)
Background: Recent epidemiological data have revealed a dramatically rising prevalence and incidence of inflammatory bowel diseases (IBD) in Mainland China, a rapidly growing industrialized region, over the last two decades. Objectives: We performed a systematic review to investigate the changing trends in the incidence of IBD in Mainland China and summarized the recent findings in risk factors associated with Chinese IBD. Methods: Relevant references were obtained from an electronic database search via MEDLINE and EMBASE (for English literatures), the China Academic Journals Full-text Database and the China Science Periodical Database in Wanfang Data (for Chinese literatures). Results: Total 1584 abstracts in Chinese and 171 abstracts in English were collected. Eight full-text with epidemiological data, 25 with risk factor data in Chinese and 7 full-text with epidemiological data, 12 with risk factor data in English were finally identified and included for analysis. Data from included epidemiological studies has showed a striking increase in the incidence rate of IBD in Mainland China over time, and current incidence rates for IBD, UC and CD were 1.80 (IBD), 1.33 (UC) and 0.46/1000 000 (CD), though it varies among regions and ethnic minority populations. In addition, several risk factors including environmental factors, diet, intestinal infectious agents, hygiene, stress, and lifestyle have been reported to be associated with the increased incidence of Chinese IBD. Conclusion: This systematic review revealed an increased incidence of IBD in Mainland China. Although it is still lower than that in the Western world, however, China has a huge population; therefore, the total number of IBD patients might not be so little as previously thought and the disease burden of IBD in China is likely underestimated.